LEGISLATIVE HISTORY AS AN INTERPRETATIVE TOOL IN UNI- AND MULTINLINGUAL LEGAL SYSTEMS (BASED ON THE EXAMPLE OF POLAND AND THE UE) - PALUSZEK, Karolina; BIELSKA-BRODZIAK, Agnieszka (Comparative Legilinguistics, 2019)
The paper aims to analyse and compare the interpretative function of legislative history in the judicial activity of the European Court of Justice and Polish courts. The authors have analysed judgments of the respective courts, focusing on the role of legislative history in their argumentation. In the Polish and European doctrine, the usefulness of travaux preparatoires has been underestimated. Nevertheless, legislative history may provide arguments important in judicial reasoning both in uni- and multilingual legal systems. However, its importance and functions in Polish and European cases examined herein are different. The research conducted enables a better understanding of the interpretative value of legislative history in legal interpretation and can result in more frequent use of this tool in the judicial activity of national and European courts.